Cholesteatoma Surgery: An Update. (2nd September 2014) - Jung, Timothy T. K.; Brackmann, Derald E.; Dornhoffer, John L.; McKenna, Michael J.; Pothier, David D.; Roland, Peter S.
Abstract : Program Description: The goals of cholesteatoma surgery are the complete removal of disease while minimizing the risk of recurrence. A secondary goal is to optimize postoperative hearing. This miniseminar features distinguished experts in the field who will present well‐established methods of cholesteatoma surgery. Important topics, such as intact‐canal‐wall versus canal‐wall‐down surgery, recurrence prevention, use of cartilage, and management of labyrinthine fistula will then be discussed in a case‐based format. The role of endoscopes and use of magnetic resonance imaging for detection of recurrence will be discussed. Finally, ossiculoplasty techniques will be presented. Educational Objectives: (1) Perform cholesteatoma surgery as practiced by experts in the field. (2) Examine advantages and disadvantages of endoscopic techniques. (3) Incorporate various methods for preventing recurrence.